Xylocaine® 10% Pump Spray as topical anaesthetic for venepuncture pain. (4th May 2018) - van Straten, A; Murray, AA; Levin, AI
Abstract : Background: Cutaneous analgesia for venepuncture pain can be achieved using various topically applied local anaesthetic formulations. Xylocaine® 10% Pump Spray containing lignocaine hydrochloride and 95% ethanol is exclusively recommended for mucosal anaesthesia. However, this formulation is readily able to penetrate skin. This study investigated whether topical pre-treatment with Xylocaine® 10% Pump Spray could facilitate analgesia for venepuncture. Methods: A single-centre, prospective, randomised, double-blind placebo-controlled trial was conducted. One hundred patients were enrolled. The control and intervention groups had 0.5 ml saline and 0.5 ml Xylocaine® applied for 20 min to preselected venepuncture sites. Pain associated with an 18-gauge cannula venepuncture was rated on an 11-point Numerical Rating Scale. A two-point or 30% reduction in pain would be deemed clinically significant. Results: Pain scores were lower ( p = 0.001) in the Xylocaine® (median 2; 95% CI 2–3) than the saline (median 4; 95% CI 3–5) group. Moderate-to-severe pain occurred in fewer Xylocaine® (18%) than saline (42%) treated patients (relative risk 0.43, CI 0.22 to 0.48; NNT = 5). Conclusion: Topical Xylocaine® 10% Pump Spray pre-treatment provided a time-effective method of reducing venepuncture-associated pain.